Simulated human patients and patient-centredness: The uncanny hybridity of nursing education, technology, and learning to care - Ireland, Aileen V. (Nursing philosophy, 2017)
Positioned within a hybrid of the human and technology, professional nursing practice has always occupied a space that is more than human. In nursing education, technology is central in providing tools with which practice knowledge is mobilized so that students can safely engage with simulated human patients without causing harm to real people. However, while there is an increased emphasis on deploying these simulated humans as emissaries from person-centred care to demonstrate what it is like to care for real humans, the nature of what is really going on in simulation—what is real and what is simulated—is very rarely discussed and poorly understood. This paper explores how elements of postcolonial critical thought can aid in understanding the challenges of educating nurses to provide person-centred care within a healthcare culture that is increasingly reliant on technology. Because nursing education is itself a hybrid of real and simulated practice, it provides an appropriate case study to explore the philosophical question of technology in healthcare discourse, particularly as it relates to the relationship between the human patient and its uncanny simulated double. Drawing on postcolonial elements such as the uncanny, diaspora, hybridity, and créolité, the hybrid conditions of nursing education are examined in order to open up new possibilities of thinking about how learning to care is entangled with this technological space to assist in shaping professional knowledge of person-centred care. Considering these issues through a postcolonial lens opens up questions about the nature of the difficulty in using simulated human technologies in clinical education, particularly with the paradoxical aim of providing person-centred care within a climate that increasingly characterized as posthuman.